2008
DOI: 10.1002/cmdc.200800205
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Release of a Surface‐Adsorbed RGD Therapeutic from a Cleavable Peptide Anchor

Abstract: Implantation of a polymeric, ceramic, or metallic implant will unavoidably activate a response from the surrounding tissue. [1] Means to attenuate this inflammatory response at the implant site are of significant interest and currently include strategies based on surface morphology, chemical modification, or drug delivery. This response is particularly evident at the site of stent deployment, where the overproliferation of smooth muscle cells can lead to restenosis-a re-narrowing of the lumen.[2] Drug-eluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Our previous research focused on using bifunctional resulting peptides to regulate the interactions that occurred at the biological-material interface including: promotion of surface cellularization, 34 suppression of apoptosis, 36 prevention of fouling, 23,24 and, more recently, release of a therapeutic from a surface. 35 In this report, we have approached the problem of poor biological activity of PGA fibers by developing a modular IFBM peptide that is capable of binding to PGA and modifying its surface to provide biological cues that direct endothelial cell adhesion, spreading, cytoskeletal reorganization, and focal adhesion plaque formation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous research focused on using bifunctional resulting peptides to regulate the interactions that occurred at the biological-material interface including: promotion of surface cellularization, 34 suppression of apoptosis, 36 prevention of fouling, 23,24 and, more recently, release of a therapeutic from a surface. 35 In this report, we have approached the problem of poor biological activity of PGA fibers by developing a modular IFBM peptide that is capable of binding to PGA and modifying its surface to provide biological cues that direct endothelial cell adhesion, spreading, cytoskeletal reorganization, and focal adhesion plaque formation.…”
Section: Discussionmentioning
confidence: 98%
“…23,24,[34][35][36]54 These bifunctional, two-domain peptide coatings must recognize and bind both the inert surface through non-covalent physisorption, while also providing a mechanism to interact with the surrounding biology. In this fashion, these peptides create an interface that allows for appropriate biological interactions with inert materials.…”
Section: Discussionmentioning
confidence: 99%
“…While not a direct dual approach, Grinstaff et al, has also reported a similar degradation technique whereby the phage-selected peptide coatings have an incorporated enzyme recognition sequence that allows for therapeutic release from a surface, a formulation that can be easily incorporated into the peptide toolkit. 101 …”
Section: 0 Biomimetic Combined Approachmentioning
confidence: 99%
“…These stimuli include pH, ionic strength and the presence of metabolic chemicals (e.g. enzymes or antigens) [59]. Some of the most recent drug carriers respond to stimuli such as light, radiation, ultrasound and magnetic or electrical fields [1012].…”
Section: Introductionmentioning
confidence: 99%